Progress on the development of a dual-polarized dense dipole array for the SKA mid-frequency aperture array - Gilmore, J.; Davidson, David; De Vaate, J. (2016)
© 2016 European Association of Antennas and Propagation. The progress on the design of a dual-polarized dense dipole array was presented. A wide bandwidth has been realized and good cross-polarization performance for an element embedded in the infinite array has been demonstrated.